ANALISIS KEBUTUHAN PEMASANGAN ZINK ANODE UNTUK MENCEGAH KOROSI PADA LAMBUNG KAPAL KAPAL GENERAL CARGO - Sudjasta, Bambang; Suranto, Purwo Joko; Setiani, Hernia (Bina Teknika, 2018)
Needs installation of cathodic protection to prevent corrosion of the ship in the sea water medium is a must so that the ships can be used as long as possible, but the effectiveness is very limited lifespan sacrificial anode that time should be right on time. For the replacement timing becomes important to do, hull plate is first exposed areas of sea water. In this area of the hull bottom water or top area of water exposed to corrosion range. Corrosion of hull plates can lead to decline in strength and service life of ships, reducing the ship's speed and reduce safety and security of cargo and passengers. From the calculation of the aluminum anode needs indicated that there is a difference between the life of the anode replacement is supposed to 5.25 years. The number of victims aluminum anode required to ship the object of the research is based on the calculation is 12 pieces (± 44.2 kg), lower than the number of anode installed in the field about 24 pieces (108 Kg). So the amount of victims aluminum anode mounted on General Cargo Ship in the field is redundant with past-year use of 5.25 while the turn is done for 3 years. For the owners of the ship, you should use zinc or magnesium anode victim since both of these materials have an efficiency of 95 % compared to aluminum, is only 50 %.